Photocatalytic Giese‐Type Reaction with Alkylsilicates Bearing C, O‐Bidentate Ligands. Issue 22 (11th February 2021) - Morofuji, Tatsuya; Matsui, Yu; Ohno, Misa; Ikarashi, Gun; Kano, Naokazu
Abstract: Herein, a photocatalytic Giese‐type reaction with alkylsilicates bearing C, O‐bidentate ligands as stable alkyl radical precursors has been reported. The alkylsilicates were prepared in one step from organometallic reagents. Not only primary, secondary, and tertiary alkyl radicals, but also elusive methyl radicals, could be generated by using the present reaction system. The generated radicals were trapped by electron‐deficient olefins bearing various functional groups to give the desired alkyl adducts. The silicon byproduct can be recovered after the photoreaction. The radical generation process was investigated by theoretical calculations, which provided an insight into the facile generation of methyl radicals from methylsilicate bearing C, O‐bidentate ligands. Abstract : Shine on me ! Photocatalytic Giese‐type reactions with alkylsilicates bearing C, O‐bidentate ligands as alkyl radical precursors are reported. Not only primary, secondary, and tertiary alkyl radicals, but also elusive methyl radicals, can be generated under the present reaction system. This radical generation process is investigated by theoretical calculations.